Peningkatan Kemampuan Menghafal Bacaan-Bacaan Salat Menggunakan Metode Drill di SD Negeri Tancep 1 Ngawen - Satiman (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to describe the application of drill learning methods in improving the ability to memorize prayer readings in grade V students at Elementary School Tancep 1 Ngawen. This research uses action research methods with qualitative data analysis. The results of this study showed improved ability to memorize prayer readings in each cycle. The average class increase of 14.09, from a grade average of 75.13 in cycle I increased to 85.38 in cycle II. The success percentage reached 52%, from 48% in cycle I increased to 100% in cycle II. The ability to memorize mandatory prayer readings in students of Tancep 1 Ngawen State Elementary School will show better results if the application of drill methods at the beginning of Islamic studies involves more students, and teachers only as facilitators.